Response of a fibre optic long period grating operating at the phase matching turning point to the deposition of a nanostructured coating - James, Stephen W.; Topliss, Stephen M.; Cheung, Sammy C.; Tatam, Ralph P. (International Society for Optical Engineering; 1999, 2009)
The response of the transmission spectrum of a fibre optic long period grating operating near the phase matching turning point to the deposition of a nanostructured coating is investigated. The dual-resonant bands characteristic of operation in this regime are observed to show a high sensitivity to the thickness of the coating, but with opposite signs. Appropriate design of the device, based on the grating period, the refractive index and thickness of the coating and the fibre composition, can allow the sensitivity of the device to the optical thickness of the coating to be optimised.